The Characterization of the Morphological and Molecular Traits of Phaseolus coccineus in the Aniene Valley: Insights into Genetic Diversity and Adaptation - Mario Ciaffi; Anna Rita Paolacci; Martina Marcomeni; Lorenzo Coluccia; Paola Taviani; Enrica Alicandri (Plants)
This study aimed to characterize the genetic diversity and morphological traits of 32 populations of Phaseolus coccineus collected from the Aniene Valley. Quantitative seed trait analyses revealed that Mandolone accessions exhibited significantly higher seed weights and dimensions compared to Fagiolone accessions. Specifically, Mandolone accessions showed an average weight of 189.48 g per 100 seeds, with seed heights and lengths averaging 14.38 mm and 23.84 mm, respectively. In contrast, Fagiolone accessions had an average seed weight of 174.13 g, with seed heights and lengths of 13.95 mm and 22.58 mm, respectively. Molecular analysis, conducted using 9 polymorphic SSR loci, identified 53 alleles across 320 genotypes, with a mean expected heterozygosity (He) of 0.695. This indicated that there was high genetic variability within the Aniene Valley populations. The genetic diversity analysis revealed two genetic clusters corresponding to the Mandolone and Fagiolone landraces. This was supported by UPGMA, PCoA, and STRUCTURE analyses. This study highlights the need to conserve the genetic diversity within these landraces and provides a basis for the development of conservation strategies for P. coccineus germplasms in the singular ecological context of the Aniene Valley.